A Shiga Toxin-Encoding Prophage Recombination Event Confounds the Phylogenetic Relationship Between Two Isolates of Escherichia coli O157:H7 From the Same Patient - Greig, David R.; Jenkins, Claire; Dallman, Timothy J. (Frontiers in Microbiology, 2020)
We compared genomes from multiple isolations of Shiga toxin-producing Escherichia coli (STEC) O157:H7 from the same patient, in cases notified to Public Health England between 2015 and 2019. There were 261 cases where multiple isolates were sequenced from the same patient comprising 589 isolates. Serial isolates from the same patient fell within 5 single nucleotide polymorphisms (SNPs) of each other for 260/261 (99.6%) of the cases, indicating that there was little evidence of within host variation. The investigation into the 13 SNP discrepancy between one isolate pair revealed the cause to be a recombination event within a stx2a-encoding prophage resulting in the insertion/deletion of a fragment of the genome. This 50kbp prophage fragment was homologous to a prophage in the reference genome, and the short reads from the isolate that had the 50kbp fragment, mapped unambiguously to this region. The discrepant variants in the isolate without the 50kbp fragment, were attributed to ambiguous mapping of the short reads from other prophage regions, to the 50kbp fragment in the reference genome. Identification of such recombination events in this dataset appeared to be rare, most likely because the majority of prophage regions in the Sakai reference genome are masked during the analysis. Identification of SNPs under neutral selection, and masking recombination events, is a requirement for phylogenetic analysis used for public health surveillance, and for the detection of point source outbreaks. However, assaying the accessory genome by combining the use of short and long read technologies for public health surveillance, may provide insight into how recombination events impact on the evolutionary course of STEC O157:H7.